Socialization and Training on Sweet Corn Dodol Production to Enhance Creativity and Economic Independence of the Santong Mulia Community: Sosialisasi dan Pelatihan Produksi Dodol Jagung Manis untuk Meningkatkan Kreativitas dan Kemandirian Ekonomi Masyarakat Santong Mulia - Suzana Hasmi; Nanik Febrianik; Verawati Verawati (Yayasan Siti Widhatul Faeha, 2025)
The development of processed products based on local commodities is an essential strategy for increasing the added value of agricultural yields and strengthening the economic independence of rural communities. This study aims to enhance the creativity and skills of the residents of Santong Mulia Village in processing sweet corn into high-value dodol products. The implementation method includes socialization, technical training, direct demonstrations, and hands-on practice using a participatory approach. Program effectiveness was evaluated through participatory observation and an assessment of participant responses. The results indicate high enthusiasm from the 30 participants, consisting of housewives, youth, and community leaders. Participants successfully produced sweet corn dodol with good sensory qualities chewy texture, golden-yellow color, and the distinctive aroma and taste of sweet corn making it suitable as a potential village flagship product. The training activities had a positive impact on improving technical skills and opening opportunities for the development of home-based enterprises and local souvenirs. It is concluded that the program effectively increased the community’s knowledge, skills, and motivation in local food processing. Future recommendations include continuous mentoring in product packaging, branding, legal certification, and digital marketing to further support the economic independence of Santong Mulia Village